Studi Intensitas Serangan Lalat Buah (Bactrocera Spp.) pada Tanaman Jambu Kristal (Psidium Guajava L.) di Kecamatan Gerung Kabupaten Lombok Barat - Bayu Anggara; Hery Haryanto; Amrul Jihadi (Lembaga Pengembangan Kinerja Dosen, 2026)
Fruit fly infestation (Bactrocera spp.) is one of the biggest problems in Kristal guava cultivation, as it can reduce fruit quality and yield. The aim of this study was to determine the infestation severity of Kristal guava plants in the Gerung district of West Lombok. The survey was conducted in April - May 2026 using an indirect observation method. Fruit flies were captured in yellow, red, green, blue, and white sticky traps placed on 20 experimental plants in four observation blocks. The fruit fly population and the degree of fruit damage were monitored for five weeks. Infestation severity data were analyzed using a scoring system based on the extent of fruit damage. The results showed that the highest number of fruit fly catches was recorded in the first week (525 individuals), while the lowest number was recorded in the fourth week (208 individuals). The infestation severity ranged from 25.86% to 42.79% and was classified as moderate. The high intensity of the attacks in the field correlated positively with the fruit fly population on crystal guavas.